Diversity of Nonribosomal Peptide Synthetase Genes in the AnticancerProducing Actinomycetes Isolated from Marine Sediment in Indonesia - Camelia Herdini; Shinta Hartanto; Sofia Mubarika; Bambang Hariwiyanto; Nastiti Wijayanti; Akira Hosoyama; Atsushi Yamazoe; Hideaki Nojiri; Jaka Widada (Indonesian Journal of Biotechnology, 2015)
Marine actinomycetes is a group of bacteria that is highly potential in producing novel bioactivecompound. It has unique characteristics and is different from other terrestrial ones. Extreme environmentalcondition is suspected to lead marine actinomycetes produce different types of bioactive compoundfound previously. The aim of this study was to explore the presence and diversity of NRPS genes in 14anticancer-producing actinomycetes isolated from marine sediment in Indonesia. PCR amplificationand restriction fragment analysis of NRPS genes with HaeIII from 14 marine actinomycetes were doneto assess the diversity of NRPS genes. Genome mining of one species of marine actinomycetes (strainGMY01) also was employed towards this goal. The result showed that NRPS gene sequence diversity in 14marine actinomycetes could be divided into 4 groups based on NRPS gene restriction patterns. Analysisof 16S rRNA gene sequences of representatives from each group showed that all isolates belong to genusof Streptomyces. Genome mining result showed that strain GMY01 harboring 10 different NRPS geneclusters that encode secondary metabolites, as pure NRPS or hybrid between NRPS and other compounds.These results indicated that marine actinomycetes having a high potential to be developed as source ofanticancer drugs development.